JSBACH 3: The land component of the MPI Earth System Model Documentation of version 3.2 - Reick, Christian H.; Gayler, Veronika; Goll, D.; Hagemann, Steffen; Heidkamp, Marcus 1973-; Nabel, Julia Esther Marlene Sophia 1981-; Raddatz, T.; Roeckner, Erich; Schnur, R.; Wilkenskjeld, S. (Max-Planck-Institut für Meteorologie, 2021)
Why should one name a land surface model after a composer? This funny idea was brought up around 1999 by Colin Prentice, a former director of the Max Planck Institute for Biogeo- chemistry in Jena, when he and his coworker Wolfgang Knorr realized in 1999 that climate models should be "biologized". After the achievements made in the 90s by coupling atmo- spheric general circulation models with ocean circulation models, and after the successful coupling with models for ocean biogeochemistry, it was the logical next step to include the so far missing variability from the interrelation between the land carbon cycle and the cli- mate. By that time, Guy Brasseur had just taken one of the three director positions at the Max Planck Institute for Meteorology in Hamburg (MPI-M), determined to couple the ozone chemistry model MOZART originating from NCAR with the Hamburg atmospheric circulation model ECHAM. Clearly, from the Jena perspective, the Earth’s biology is at least equally important as atmospheric chemistry.
Literaturverzeichnis: Seite 269-271
Keywords: Klima-Chemie-Modell; ECHAM5; Land processes; Earth System Model; ESM; JSBACH